Program Pencegahan Obesitas Anak Dengan Perlibatan Peran Keluarga: Literature Review - Amiyani Kristina; Titih Huriah (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: To identify the role of parents in preventing obesity in children. Method: The method used in this literature review is using the Google Scholar and the Science Direct database. At the beginning of searching with keywords: “((prevention OR prevent OR precautions) AND (obesity) AND (children OR childhood OR pediatric))”, the results of 6 international articles were found from the range of 2016 to 2018 which corresponded to the inclusion and exclusion criteria. Results: Efforts to prevent obesity can be made by involving the role of parents, that is the role of the father to be fully responsible for instilling healthy habits in children. Besides, it is also necessary to see the involvement of the role of parents who experience stress and low income which can be a cause of obesity in children by applying attention-based parents awareness and treatment efforts involving families and health services to increase awareness in reducing the risk of obesity. Conclusion: The understanding of parents about the risk of obesity in children is very important, also about the effectiveness of parenting applied to the family, parenting competencies that parents have, ability to control their children, and parental satisfaction in applying parenting patterns to children with obesity.Keywords: Role of Parents, Prevention, Obesity, Children